Strengthening Economic Education Quality as a Pathway to Achieving the Sustainable Development Goals in Indonesia - Sudarno Sudarno; Romi Siswanto; Rintatik Wahyuningsih; Syukri Fathudin Achmad Widodo (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to support the achievement of the Sustainable Development Goals (SDGs), particularly the fourth goal on quality education, by improving the quality of Economics Education in Indonesia, which is currently considered suboptimal. This study uses a library research method with a qualitative descriptive approach. Data were obtained through a systematic review of various scientific sources, including national and international journals, scientific articles, and relevant documents related to Economics Education and the SDGs. The results of the study indicate that the quality of Economics Education in Indonesia still faces various structural and pedagogical challenges. The main problems include the uneven quality of Economics Education across regions, low professionalism and capacity of educators, limited allocation of learning time, and a learning approach that tends to be narrow and cognitively oriented with monotonous methods. These conditions have an impact on the low quality of the learning process and student learning outcomes in Economics subjects. To address these problems, this study recommends several strategies, including increasing public trust in Economics Education, developing a curriculum relevant to community needs and global developments, providing adequate educational facilities and infrastructure, utilizing technology in the learning process, and improving teacher competency in the use of technology and digital learning resources, including digital libraries. The implementation of this strategy is expected to improve the quality of Economic Education in Indonesia and contribute significantly to the achievement of the SDGs in the field of education, namely the provision of quality, equitable, and sustainable education for the entire community